Evaluation of Plasma Soluble Cd40 Ligand Levels in Children with Familial Mediterranean Fever and Its Relationship with Carotid Intima–Media Thickness - Sukriye Ozde; Cansu Mehdizade; Ozel Mehmet Ali; Cem Ozde; Osman Kayapinar; Muferret Erguven (Diagnostics)
Background/Objectives: It has been suggested that chronic inflammatory diseases may be associated with an increased risk of cardiovascular disease. In this study, we investigated plasma soluble CD40 ligand (sCD40L) levels and their association with carotid intima–media thickness (cIMT) in children with Familial Mediterranean fever (FMF). Methods: The study was designed as a prospective cross-sectional study. The study included 68 asymptomatic children aged 5–18 years with FMF, diagnosed according to Tel Hashomer criteria, who were followed up regularly for at least one year, receiving regular colchicine treatment and not in an acute exacerbation period, along with 65 healthy children with similar demographic characteristics. cIMT was assessed by ultrasound and plasma sCD40L levels were measured by sandwich ELISA in all children. Results: Erythrocyte sedimentation rate, high-sensitivity C-reactive protein and serum amyloid A levels were not significantly different between patients and controls. However, sCD40L (p = 0.004) and fibrinogen (p = 0.011) levels were significantly higher in the FMF group compared to the control group. No significant difference was found between the patient and control groups in terms of carotid intima–media thickness (p = 0.517). Multivariate logistic regression was performed to assess the independent associations of fibrinogen and sCD40L with FMF. The results of this analysis indicated that sCD40L, but not fibrinogen, demonstrated a significant association with FMF (odds ratio [OR]: 1.003, 95% confidence interval [CI]: 1.001–1.006, p = 0.011). To determine the diagnostic performance of sCD40L, a receiver operating characteristic (ROC) curve was generated. This analysis demonstrated that sCD40L levels exceeding 100 pg/mL were predictive of FMF, yielding a sensitivity of 70.6% and a specificity of 62.3%. The positive predictive value and negative predictive value were 55.4% and 64.3%, respectively. The area under the curve for sCD40L was 0.644 (95% CI: 0.549–0.738, p = 0.004), signifying a statistically significant predictive capacity. Plasma sCD40L levels were significantly higher in FMF children with the M694V mutation (p = 0.013). Conclusions: The results of this study suggest that the high plasma sCD40L levels found in children with FMF may be related to the inflammatory activation of the disease rather than to atherosclerosis.